IDENTIFIKASI JENIS BIJI KOPI MENGGUNAKAN EKSTRAKSI FITUR TEKSTUR BERBASIS CONTENT BASED IMAGE RETRIEVAL - Prastyaningsih, Yunita; Noor, Agustian; Supriyanto, Arif (Fakultas Teknik, Universitas Tadulako, 2020)
Every type of coffee have a different shape, texture, calor based on roasting system used and the taste is quite significant. It makes coffee beans have different price. However, not all of coffee shop owners and coffee farmer can identify the type of coffee beans by only looking these coffee beans. So, it can lead something wrong to identify the type of coffee beans If the coffee shop owners don't have enough knowlegde aboutÂ coffee beans. Identifying the type of coffee with the naked eye is difficult to distinguish so that special expertise is needed, one of the methods can be used to identify the type of coffee is digital image processing such as CBIR (content based image retrieval) which aims to identify the characteristic or feature of the object, this method used to do feature identification process, one of them is the texture feature that are owned by severay types of coffee. Extraction of texture feature is used by using GLCM ( gray level co-occurrence matrix), the dataset used is an image of coffee beans taken from 3 types, namely, robusta coffee beans, Arabica coffee beans and liberica coffee beans. The amount dataset used is 165 images. The CBIR system is able to identify the types of coffee beans by precision value 55.20%.